Egypt’s Medicinal and Aromatic Plants (MAPs) Clusters: Unleashing untapped potentials of Egypt’s agribusiness sector - Abdelaziz, Fatma (2019)
As part of Egypt’s Network for Integrated Development (ENID/ElNidaa) 2019 annual conference.